Effect of Acute Resistance Exercise and Resistance Exercise Training on Central Pulsatile Hemodynamics and Large Artery Stiffness: Part II - Denis J. Wakeham; Gary L. Pierce; Kevin S. Heffernan (Pulse)
Background: In part one of this two-part series, we performed a detailed analysis of the hemodynamic signature produced during resistance exercise (RE) and discussed the subacute effects on short-term modulation of large artery stiffness and central pulsatile hemodynamics. In this second part of our two-part series, we consider the subacute recovery window as the driver of resistance exercise training (RET) adaptations. We then discuss the results of RET interventions and corroborate these findings against the information gleaned from cross-sectional studies in habitually strength-trained athletes. Finally, we explore associations between muscular strength and arterial stiffness. Summary: Our reanalysis of key studies assessing arterial stiffness in the hour post-RE suggests changes in both load-dependent and load-independent indices of arterial (aortic) stiffness. Regarding adaptations to habitual RET, a growing body of evidence contradicts earlier findings that suggested RET increases large artery stiffness. Recent meta-analyses conclude that longitudinal RET has no effect or may even reduce large artery stiffness. However, cross-sectional studies continue to support early RET intervention studies and note that habitual RET may increase large artery stiffness and central pulsatile hemodynamics. Complex interactions between vascular smooth muscle cells and the extracellular matrix may offer insight into inter-individual heterogeneity in subacute responses and chronic adaptations to acute RE and habitual RET. Key Messages: Habitual RET is fundamentally important for skeletal muscle quality and quantity as well as cardiovascular function. Recent literature suggests that habitual RET has negligible effects on large artery stiffness and central hemodynamic pressure pulsatility, but cross-sectional observations still raise questions about the chronic large artery effects of habitual RET. Background: In part one of this two-part series, we performed a detailed analysis of the hemodynamic signature produced during resistance exercise (RE) and discussed the subacute effects on short-term modulation of large artery stiffness and central pulsatile hemodynamics. In this second part of our two-part series, we consider the subacute recovery window as the driver of resistance exercise training (RET) adaptations. We then discuss the results of RET interventions and corroborate these findings against the information gleaned from cross-sectional studies in habitually strength-trained athletes. Finally, we explore associations between muscular strength and arterial stiffness. Summary: Our reanalysis of key studies assessing arterial stiffness in the hour post-RE suggests changes in both load-dependent and load-independent indices of arterial (aortic) stiffness. Regarding adaptations to habitual RET, a growing body of evidence contradicts earlier findings that suggested RET increases large artery stiffness. Recent meta-analyses conclude that longitudinal RET has no effect or may even reduce large artery stiffness. However, cross-sectional studies continue to support early RET intervention studies and note that habitual RET may increase large artery stiffness and central pulsatile hemodynamics. Complex interactions between vascular smooth muscle cells and the extracellular matrix may offer insight into inter-individual heterogeneity in subacute responses and chronic adaptations to acute RE and habitual RET. Key Messages: Habitual RET is fundamentally important for skeletal muscle quality and quantity as well as cardiovascular function. Recent literature suggests that habitual RET has negligible effects on large artery stiffness and central hemodynamic pressure pulsatility, but cross-sectional observations still raise questions about the chronic large artery effects of habitual RET.